Ukuran Populasi Efektif, Ukuran Populasi Aktual dan Laju Inbreeding Per Generasi Itik Lokal di Kecamatan Tilatang Kamang Kabupaten Agam - Rusfidra Rusfidra; R Zein; A. M. A. Hasibuan (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
This study aims to obtain the effective population size, actual population size and rate of inbreeding of Kamang local duck. In this study used a sample local duck raised from 30 farmers. This research conducted was survey method with purposive random sampling. The variables were calculated in the study, namely the number of adult male ducks (Nm), number of adult female ducks (Nf), number of young male and young female ducks, number of male and female ducklings, actual population size (Na), effective population size (Ne), and the rate of inbreeding per generation (ΔF). The research was conducted in the District Tilatang Kamang of Agam Regency began on December 23, 2011 until January 25, 2012. The study concluded that the local duck population in the District Tilatang Kamang was 4.131 head. The highest populations were in Nagari Koto Tangah had 1.626 head of ducks. The structure population of the Local duck in the District Tilatang Kamang was an adult male ducks (11.73%), adult female ducks (24.88%), young male ducks (12.44%), young female ducks (13.12%), drake (13.58%), and female ducks (13.58%). Effective population size (Ne) Kamang Local ducks was 1.310 head and the rate of inbreeding per generation is 0.04%.